Effect Of Multi-Walled Carbon Nanotubes And Surfactants Towards Micro-Crack Using Acoustic Emission Technique - Ali, Yousefi (2019)
Growth and accumulation of micro-cracks result in formation of cracks at macro scale which allow penetration of water and deleterious chemicals to the cement matrix. Hence, it is essential to limit the development of cracks at the early stages and once they are at micro-scale to extend the durability of concrete structures. This study aims to investigate the effect of various types surfactant on dispersion of Multi-walled carbon nanotubes (MWCNTs) as well as the influence of different concentrations of MWCNTs on the engineering and mechanical properties of cement mortar as well as the growth of internal micro-cracks in MWCNT-cement mortar using acoustic emission (AE) technique. Different mechanical tests including flow test, ultrasonic test, compressive and flexural test as well as characterization test such as UV-visible spectroscopy, Field Emission Scanning Electron Microscope (FESEM) and Transmission Electron Microscopy (HRTEM) were employed to evaluate the properties of MWCNT-cement composites. In addition, AE technique was used to independently validate the mechanical performance and growth of micro-cracks in the MWCNT-cement mortar. The characterization tests showed a satisfactory level of dispersion and stability for the used surfactants. The results of mechanical tests showed significant improvements in compressive strength and flexural properties of cement mortars reinforced with MWCNTs. Moreover, the microstructure observation of MWCNT-cement mortars demonstrated that MWCNTs effectively bridging micro-cracks within the cement matrix. Besides, the AE analysis confirmed that MWCNTs can limit the initiation of micro-cracks and delay the propagation and growth of micro-cracks.